2019
DOI: 10.2147/cmar.s204729
|View full text |Cite
|
Sign up to set email alerts
|

<p>Whole-brain helical tomotherapy with integrated boost for brain metastases in patients with malignant melanoma – final results of the BRAIN-RT trial</p>

Abstract: Background: Patients with multiple brain metastases (BMs) from malignant melanoma have a poor prognosis. Recent developments in radiation techniques allow simultaneous integrated boost (SIB) concepts while sparing organs at risk. Data on conventional versus dose-escalated radiation approaches in multiple BMs from malignant melanoma are warranted. Methods: In this prospective, single-center, randomized two-armed study (trial ID: DRKS00005127), patients with multiple BMs from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Of the three RCTs, none reported how their randomisation sequence was generated but all reported complete outcome data and clinically-relevant outcomes. Two of the three trials 28 , 29 were closed early due to poor accrual and had sample sizes of 7 and 18, greatly limiting the reliability of their results. Baseline characteristics for the different treatment arms were reported and similar for the trial of 18 patients 29 but were not reported for the trial of 7 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three RCTs, none reported how their randomisation sequence was generated but all reported complete outcome data and clinically-relevant outcomes. Two of the three trials 28 , 29 were closed early due to poor accrual and had sample sizes of 7 and 18, greatly limiting the reliability of their results. Baseline characteristics for the different treatment arms were reported and similar for the trial of 18 patients 29 but were not reported for the trial of 7 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline characteristics for the different treatment arms were reported and similar for the trial of 18 patients 29 but were not reported for the trial of 7 patients. 28 The largest trial 30 had 215 patients, and while not stratifying for previous treatments, randomisation was effective as previous treatments were well balanced between the two study arms, as were baseline characteristics. This trial provided the most reliable data for identifying the effects of adjuvant WBRT in conjunction with surgery and/or SRS for patients with 1–3 brain metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs compared hippocampal avoidance-WBRT with conventional WBRT. [22][23][24] The studies could not be combined because they did not report the same outcomes; 2 of the studies were determined to be highrisk, one low risk of bias. The low risk of bias NRG CC001 trial found no significant difference in overall or intracranial-progression free survival and no significant differences in quality of life.…”
Section: Wbrt With Neuroprotectionmentioning
confidence: 99%
“…However, comparing patients treated with hippocampal avoidance WBRT with memantine versus those treated with WBRT with memantine, hippocampal avoidance WBRT was associated with a lower risk of cognitive failure, with less deterioration of executive function and learning and memory. 24 A trial reported by Hauswald et al 22 was stopped early, and quality of life data were not analyzable. Yang et al concluded that hippocampal-avoidance WBRT has better preservation of late verbal memory, but not in verbal fluency or executive function.…”
Section: Wbrt With Neuroprotectionmentioning
confidence: 99%
“…The target volume is irradiated using a fan beam with rotating linac continuously moving the treatment couch. With this special helical design, HT can achieve comparable or better plan quality than conventional VMAT, which is used for a limited number of brain metastases [ 26 ]. Several studies compared HT and VMAT for different sites, and mixed results were reported [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%